DNA BARCODING of Zingiber loerzingii Valeton USING Ribulose-1,5-biphosphate Carboxylase-Oxygenase Large subunit Gene (rbcL) GENE LOCUS - Ladiez Rahmayani Sagala; Lazuardi Lazuardi; Fauziyah Harahap; Kartika Manalu; Zahratul Idami; Eko Prasetya (JBIO: jurnal biosains (the journal of biosciences), 2022)
DNA barcode is one of the molecular techniques used to identify and classify living things. Z. loerzingii is currently reported as a rare and endemic plants that is only found in North Sumatra. Scientific studies for Z. Loerzingii is measly done so that the information about this plant is limited while a clear identity on a plant is essential to discover the potential. This study aims to determine the molecular characteristics of Z. loerzingii by using DNA barcodes and assessing the phylogenetic relationship based on the rbcL gene locus. DNA was isolated with a commercial kit. The rbcL gene locus in the chloroplast genome of Z. loerzingii amplified using the Polymerase Chain Reaction technique to produce amplicon with the length approximately 600 bp. Consensus sequence merging generate a sequence with 576 bp length. The phylogenetic tree reconstruction was carried out using the Neighbor-Joining method and the Kimura-2-Parameter calculation model showed Z. loerzingii included in the monophyletic group with Zingiber mioga and Zingiber officinale as the sister taxa. The results for the molecular diversity analysis of Z. Loerzingii point out that in all samples of Z. loerzingii which collected from Cagar Alam Sibolangit have no molecular or genetic diversity. Therefore, it can be concluded that DNA barcoding with the rbcL gene locus can be used as a method to identify Z. loerzingii molecularly and efficient in determining their phylogenetic with other species.